Роль гомеостатистических механизмов в формировании результативности платинолечения больных с раком яичника = Role homeostatistic mechanisms in the formation of performance platinum treatment of patients with ovarian cancer - Rybin, A. I. (Journal of Education, Health and Sport, 2016)
Rybin A. I. Роль гомеостатистических механизмов в формировании результативности платинолечения больных с раком яичника = Role homeostatistic mechanisms in the formation of performance platinum treatment of patients with ovarian cancer. Journal of Education, Health and Sport. 2016;6(6):405-414. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.55835 http://ojs.ukw.edu.pl/index.php/johs/article/view/3593 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 16.06.2016. РОЛЬ ГОМЕОСТАТИСТИЧЕСКИХ МЕХАНИЗМОВ В ФОРМИРОВАНИИ РЕЗУЛЬТАТИВНОСТИ ПЛАТИНОЛЕЧЕНИЯ БОЛЬНЫХ С РАКОМ ЯИЧНИКА А. И. Рыбин Одесский национальный медицинский университет Реферат Автор, на основании анализа результатов исследования гомеостатистических механизмов (детоксикационная функция печени, цикл оксида азота; обмен серусодержащих аминокислот) у 121 больной раком яичника и разной чувствительностью к препаратам платины, приходит к заключению, что реализация генетически определенной чувствительности рака яичника к препаратам платины связана с этими механизмами. Автор полагает, что активность цикла оксида азота влияет на уровень эндогенной интоксикации и устойчивость организма к внешним воздействиям. Уровень содержания SS-SH групп и их связь с белковыми или липопротеидными комплексами, очевидно, определяет уровень сульфид-платиновых комплексов, а состояние детоксикационной системы, возможно, определяет жизни таких комплексов и эффективность лечения, соответственно. Ключевые слова: рак яичника, гомеостатические механизмы; SS-SH группы, оксид азота. ROLE hOMEOSTATISTIC MECHANISMS IN THE FORMATION OF PERFORMANCE PLATINUM TREATMENT OF PATIENTS WITH OVARIAN CANCER A. I. Rybin Odessa National Medical University Abstract The author, based on the analysis results of the study gomeostatisticheskih mechanisms (liver detoxification function, nitric oxide cycle, exchange of sulfur-containing amino acids) in 121 patients with ovarian cancer and different sensitivities to drugs of platinum, comes to the conclusion that the implementation of a genetically determined sensitivity of ovarian cancer to the drugs of platinum associated with these mechanisms. The author believes that the activity of nitric oxide cycle affect the level of endogenous intoxication and the body’s resistance to external influences. The level of SS-SH groups content and their relation to protein or lipoprotein complexes, obviously determines the level of sulphide-platinum complexes, and the state of detoxification system may determine the lifetime of such systems and the effectiveness of treatment, respectively. Keywords: ovarian cancer, homeostatic mechanisms; SS-SH group, the nitrogen oxide.